2010
DOI: 10.1103/physrevb.81.155454
|View full text |Cite
|
Sign up to set email alerts
|

Surface and grain-boundary scattering in nanometric Cu films

Abstract: We report a quantitative analysis of both surface and grain-boundary scattering in Cu thin films with independent variation in film thickness ͑27 to 158 nm͒ and grain size ͑35 to 425 nm͒ in samples prepared by subambient temperature film deposition followed by annealing. Film resistivities of carefully characterized samples were measured at both room temperature and at 4.2 K and were compared with physical models that include the effects of surface and grain-boundary scattering. Grain-boundary scattering is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

23
166
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(190 citation statements)
references
References 30 publications
23
166
1
Order By: Relevance
“…We also examined our own new experimental data on NbN thin films. In these data, relating dT c to R s provided fits with reduced scatter relative to fits suggested by previous models [7][8][9][10][30][31][32]. Finally, we supply two possible explanations of the observed universal behavior.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…We also examined our own new experimental data on NbN thin films. In these data, relating dT c to R s provided fits with reduced scatter relative to fits suggested by previous models [7][8][9][10][30][31][32]. Finally, we supply two possible explanations of the observed universal behavior.…”
mentioning
confidence: 61%
“…Figures 1(a) and 1(b) show the dependence of T c on thickness and on sheet resistance for our NbN films, allowing a comparison of the data with the existing models [7][8][9][10][30][31][32]. Although a general trend can be seen in both T c (d) and T c (R s ), Chemical treatment of the substrate prior to deposition is suspected of influencing the properties of the red solid points here and in Fig.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Prior work by Sun et al [2][3][4] on SiO 2 and Ta/SiO 2 -encapsulated nanometric Cu films showed grain-boundary scattering to be the dominant mechanism contributing to the resistivity increase related to the classical size effect. These studies also showed a weaker, but still significant, contribution from surface scattering.…”
Section: Introductionmentioning
confidence: 96%
“…[10][11][12] As a result, by adding several nanometers of a low conductivity tantalum nitride barrier layer (~10 6 S/m) onto Cu (5.96 × 10 7 S/m), the effective width of a Cu wire would be decreased by 10 -20 %, thus drastically decreasing the overall conductivity of the nanoscale interconnects. [13][14] Therefore, a high-conductivity metallic material with Cu stabilization functionalities is needed for furtherdown-sized microelectronic interconnects.…”
Section: Introductionmentioning
confidence: 99%